Magnetic field of tubular linear machines with dual Halbach array - Yan, Liang (2013)
Permanent magnet (PM) array affects flux field distribution of electromagnetic linear machines significantly. A novel dual Halbach array is proposed in this paper to enhance flux density in air gap, and thus to improve output performance of linear machines. Magnetic field in three-dimensional (3D) space of a tubular linear ma- chine with dual Halbach array is formulated based on Laplace's and Poisson's equations. Numerical result from finite element method is employed to simulate and observe the flux distribution in the machine. A research prototype and a testbed are developed, and experiments are conducted to validate the analytical models. The study is useful for analysis and design optimization of electromagnetic linear machines.